HAEMOGLOBIN AND PLASMA BIOCHEMICAL PROFILE OF REPEAT BREEDER CATTLE ON THE DAY OF ESTRUS COULD PLAY A ROLE IN EXHIBITION OF ESTRUS AND SUBSEQUENT PREGNANCY OUTCOME - KUNDE, A A S; RAJU, M S; MURUGAVEL, K; THANISLASS, J (The Indian Journal of Animal Reproduction, 2022)
On the day of induced estrus, jugular vein blood samples were collected from healthy repeat breeder cattle (n=45) for the estimation of haemoglobin, glucose, cholesterol and total protein, followed by pregnancy diagnosis on day 45 post-insemination. There was no difference (p<0.05) in haemoglobin, plasma cholesterol and plasma total protein in animals showing weak, intermediate or intense estrus, however, plasma glucose was high (p<0.05) in animals exhibiting intense estrus compared to their counterparts exhibiting intermediate estrus. Between pregnant and non-pregnant counterparts, plasma total protein was high (p<0.05) on the day of induced estrus in the former, whereas other blood/plasma parameters were similar (p>0.05). In brief, plasma biochemical profile of repeat breeder cattle on the day of estrus could play a role in exhibition of estrus and subsequent pregnancy outcome.